Teknik Assertiveness Training dalam Penurunan Perilaku Kekerasan pada Pasien Skizoprenia di RS. Jiwa Prof. Dr. Muhammad Ildrem Medan - Purwaningsih Purwaningsih; Ade Irma Khairani; Tio Elisa Marlina Lubis (Jurnal Riset Hesti Medan, 2021)
Violent behavior is a form of aggressive or violent behavior that is shown verbally, physically or both to an object, other person or self that leads to the potential to be destructive or actively causes pain, danger and suffering. Assertiveness training is the application of behavioral training with the aim of assisting individuals in developing direct ways of relating in interpersonal situations. The increasing number of schizophrenic mental patients with violent behavior will have an impact on families and communities in the form of an economic burden and a decreased quality of life in carrying out daily activities. Qualitative research with assertiveness training technique is carried out as an application of behavioral training with the aim of helping individuals develop ways of direct contact in interpersonal situations. Based on the stages of applying assertive training techniques through group guidance, it shows that there is an increase in the patient's ability to express every problem he is facing. So it can be concluded that the implementation of assertive training techniques in revealing real patient problems through group activity guidance in hospitals. Hospital of Prof. Dr. Muhammad Ildrem Medan there have been developments and improvements.Violent behavior is a form of aggressive or violent behavior that is shown verbally, physically or both to an object, other person or self that leads to the potential to be destructive or actively causes pain, danger and suffering. Assertiveness training is the application of behavioral training with the aim of assisting individuals in developing direct ways of relating in interpersonal situations. The increasing number of schizophrenic mental patients with violent behavior will have an impact on families and communities in the form of an economic burden and a decreased quality of life in carrying out daily activities. Qualitative research with assertiveness training technique is carried out as an application of behavioral training with the aim of helping individuals develop ways of direct contact in interpersonal situations. Based on the stages of applying assertive training techniques through group guidance, it shows that there is an increase in the patient's ability to express every problem he is facing. So it can be concluded that the implementation of assertive training techniques in revealing real patient problems through group activity guidance in hospitals. Hospital of Prof. Dr. Muhammad Ildrem Medan there have been developments and improvements.